Faculty advisor program for family medicine residents. - Nasmith, L. (College of Family Physicians of Canada, 1997)
PROBLEM BEING ADDRESSED: In response to the accreditation guidelines of the College of Family Physicians of Canada's (CFPC) Task Force on Intraining Evaluation, the Department of Family Medicine at McGill University implemented a faculty advisor program on July 1, 1993. OBJECTIVE OF PROGRAM: In addition to meeting the requirements of the CFPC, the faculty advisor program was developed to foster communication between residents and faculty, increase opportunities for feedback, promote self-directed learning, and personalize the educational experience of trainees. MAIN COMPONENTS OF PROGRAM: Residents were assigned an advisor. They were expected to meet their advisors monthly to discuss educational objectives, performance, career planning, and any problems. Educational plans were to be completed at each meeting. CONCLUSIONS: Feedback from advisors and residents has been positive, with both groups expressing overall satisfaction with the program. The faculty advisor program will continue but will be modified to address problems identified and better meet the needs of faculty and residents.